Sport impact on patients with psoriasis and psychiatric problems - Sambura, Maria; Rosołowska-Żak, Sara; Sas, Wiktoria; Podyma, Katarzyna; Ryznar, Gracja; Rejdych, Julia; Pierzchała, Piotr; Minkowska, Michalina; Chimiak, Krystyna; Bylica, Gabriela (Quality in Sport, 2024)
Introduction: Psoriasis is a systemic inflammatory disease with an immunological basis. The estimated number of people suffering from psoriasis is 60 million. Despite the large number of patients with this diagnosis, the question of which mechanisms are mainly responsible for its development has not yet been answered. One theory is that a change in the patient's psychological state acts as a trigger for the manifestation and worsening of the disease. Another unresolved issue is the relationship between sports and psoriasis. While some studies suggest exercise might worsen symptoms, others highlight potential benefits like improved quality of life. Aim of the study : The aim of our study is to present connection between mental state of patients and occurance of psoriasis. Additionally, the study aims to elucidate the potential benefits of integrating psychological interventions and physical activity into psoriasis management strategies, with the goal of improving patient outcomes and enhancing overall quality of life. Material and methods : We searched electronic databases, using keywords such as „Psoriasis”, „Depression” and „Psoriasis and sport ”. Conclusions : Psoriasis stands as a profound example of the intricate interplay between physical health and mental well-being. The findings presented in this paper underscore the importance of a holistic approach to psoriasis management, integrating dermatological, psychological, and physical interventions.